REINTERPRETATION OF THE MEANING OF THE HADITH ON PROHIBITION FOR WOMEN TO TRAVEL WITHOUT A MAHRAM: The Ma’na-cum-Maghza Approach - Fuaddin, Achmad; Imam Mutaqin, Muhammad (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
One of the interesting objects of study to be researched in the current era is related to gender issues. One of the interesting gender issues is related to the hadith which prohibits a woman from traveling except with her mahram or husband. The scholars in responding to this hadith tend to establish strict laws, namely, it is forbidden for women to travel alone. This is interesting to study because now many women are traveling alone due to many reasons, such as economic and educational problems. Therefore, the authors are interested in researching and reinterpreting the meaning of the prohibition of traveling for women except with their husbands or mahrams using the ma’na-cum-maghza approach. This aims to determine the historical significance of hadith and its significance today. The results of this study indicate that women are prohibited from traveling alone without being accompanied by a mahram or husband due to safety factors that were not guaranteed at the time of the Prophet. As for traveling today, if it is safe to travel alone, it is permissible for a woman to travel alone. However, if the current situation is dangerous on the road or at the destination and a woman can’t travel alone, then there must be someone who can look after her.[Salah satu obyek kajian yang menarik untuk diteliti di era sekarang adalah terkait isu-isu gender. Salah satu isu gender yang menarik adalah terkait hadis yang melarang seorang wanita melakukan safar (bepergian) kecuali bersama mahram atau suami. Para ulama dalam menyikapi hadis tersebut cenderung menetapkan hukum ketat, yaitu dilarang bagi perempuan melakukan bepergian sendirian. Hal ini menarik untuk dikaji dikarenakan pada kenyataanya sekarang banyak wanita yang melakukan safar sendirian dikarenakan banyak alasan, seperti masalah ekonomi dan pendidikan. Oleh karena itu penulis tertarik untuk meneliti dan mereinterpretasi pemaknaan larangan safar bagi perempuan kecuali bersama suami atau mahram dengan menggunakan pendekatan ma’na-cum-maghza. Hal ini bertujuan untuk mengetahui signifikasi historisitas hadis di zaman sekarang. Hasil penelitian ini menunjukkan larangan perempuan untuk melakukan safar sendirian tanpa ditemani mahram atau suami dikarenakan faktor keamanan yang tidak menjamin pada zaman Nabi. Adapun bepergian pada zaman sekarang jika sudah terjamin keamanannya untuk melakukan safar secara sendirian, maka diperbolehkan seorang perempuan melakukan safar sendiri. Namun jika keadaan zaman sekarang terdapat bahaya di jalan maupun tempat tujuan dan tidak memungkinkan seorang perempuan untuk bepergian sendirian, maka harus ada seseorang yang bisa menjaganya.]